Dynamic viscoelastic characterisation of ostrich-meat yor (Thai sausage) following pressure, temperature and holding time regimes - Utaiwan Chattong (2018)
Ostrich-meat yor (Thai sausage) was pressurized at 200, 400 and 600 MPa, with 40 and 50 °C for 40 or 60 min, subsequently, the products were assessed by stress control rheometry. Two types of viscoelastic measurement were made. The first was an oscillatory analysis performed at a frequency range of 0.01-10 Hz using a stress of 30 Pa. Secondly, creep and recovery testing was performed with an initial load of 30 Pa for 300 s, unloaded recovery 900 s. Finally, the products were subjected to sensory evaluation using a 9-point hedonic scale. To support the rheological measurement, SDS-PAGE electrophoretic analysis was also applied. The viscoelastic characterisation of all treated ostrich-meat yor showed that G′ was larger than G″ with small tan δ values (0.23) and the difference between G′ and G″ of each plot was relatively one log cycle. These indicated solid-like behaviour with the predominance of an elastic component. Whereas all creep curves of the treated samples were best characterised by a four-element "Burgers" model in which the J0data and retardation time (λret) suggested that increasing pressure levels, temperature and holding time significantly affected the viscoelastic properties of the samples. The electrophoregrams indicated that these structural changes which might be associated with the formation of hydrophobic interactions and disulphide bonding. Most sensory attributes of the pressure treated products received higher scores than conventionally steamed products. © 2008 Elsevier Ltd. All rights reserved.